MENINGKATKAN KEMAMPUAN GURU DALAM MENERAPKAN MODEL -MODEL PEMBELAJARAN MELALUI KEGIATAN SUPERVISI KELAS DI SMPN 2 JAYANTI - Warso, Eko (STAI Darul Qalam Tangerang, 2021)
In carrying out the learning process at school, a teacher should be good at choosing a learning model that is in accordance with the learning material. In general, teachers rarely use learning models in every learning process because of the teacher's lack of understanding about learning models that can facilitate teachers in implementing the learning process in the classroom. With this research the formulation of the problem is whether the motivation of teachers to apply learning models can improve the teaching ability of teachers at SMP Negeri 2 Jayanti. Based on the results of the study, it can be concluded that using learning models in the teaching and learning process can increase teacher teaching motivation and student learning. This is evident in the first cycle of all teachers (nine people) including the assessment of learning outcomes in the lesson plans for the application of learning models even though the sub-components (techniques, instrument forms, questions), scoring guidelines, and answer keys are incomplete. If it's a percentage, 56%. each teacher got a score of 1 and 3 (less good and good), three people got a score of 2 (good enough), and one person got a score of 4 (very good). In the ninth cycle, the teacher included an assessment of learning outcomes in the lesson plans for the application of the learning models even though there were teachers who were still wrong in determining the technique and form of the assessment. Seven people got a score of 3 (good) and one person got a score of 4 (very good). If it is a percentage, 78%, there is an increase of 22% from cycle I